The Relationship Between Admission Blood Pressure and Clinical Outcomes for Acute Basilar Artery Occlusion - Cao, Yuhong; Li, Rongzong; Jiang, Shunfu; Guo, Jing; Luo, Xiaojun; Miao, Jian; Liu, Jincheng; Zheng, Bo; Du, Jie; Zhang, Yuxian; Yang, Shunyu; Wang, Li; et al. (Frontiers in Neuroscience, 2022)
Abstract Background and purpose: Optimal blood pressure management of patients with basilar artery occlusion (BAO) remains uncertain. This study aimed to investigate the relationship between admission blood pressure and clinical outcomes following acute BAO. Materials and methods: We analyzed data from a prospective, nationwide cohort study of 829 patients with acute BAO and posterior circulation stroke. Baseline systolic blood pressure (SBP) and diastolic blood pressure (DBP) were recorded on admission. The primary outcome was neurological functional disability based on the modified Rankin Scale (mRS) score at 90 days. Secondary outcomes included successful reperfusion, mortality within 90 days, and National Institutes of Health Stroke Scale (NIHSS) score change. Multivariable logistic regression was used to assess the associations of SBP and DBP with outcomes. Results: We include 829 patients with posterior circulation stroke and BAO between January 2014 and May 2019. Multivariate logistic regression showed high SBP and DBP correlated with unfavorable outcomes. The favorable prognosis (mRS ≤3) rates of the low-to-normal and the hypertension groups were 34.8% and 23.9%, respectively. After adjusting for covariates, multivariate regression analysis demonstrated that an SBP >140 mmHg was associated with a poor functional outcome (adjusted OR [aOR], 1.509; 95% CI, 1.130–2.015) and mortality at 90 days (aOR, 1.447; 95% CI, 1.055–1.985), and predicted a lower probability of successful reperfusion (aOR, 0.550; 95% CI, 0.389–0.778). The risk of symptomatic intracranial hemorrhage and the NIHSS score at 24 hours were not significantly different between the high SBP group and the low-to-normal blood pressure group. And the results for DBP were similar. Conclusions: Among patients with acute BAO, higher systolic or diastolic blood pressure at admission was associated with poor stroke outcomes and had a lower probability of successful reperfusion, with an increased risk of mortality.